Treatment and outcomes for synovial sarcoma patients in Western Australia: the role of neoadjuvant chemoradiotherapy. Issue 6 (3rd September 2020) - Khan, Yasir; Carey‐Smith, Richard; Taylor, Mandy; Woodhouse, Jennifer; Jacques, Angela; Wood, David; Long, Anne
Abstract: Background: This is a retrospective review of synovial sarcoma (SS) patients treated over the last 12 years in Western Australia (WA). SS is both chemo and radiotherapy sensitive. Results of trials in adjuvant chemotherapy are conflicting and there is limited support for neoadjuvant chemotherapy. The use of combined chemoradiotherapy is based on institutional preferences. Aim: We reviewed the outcomes for SS patients treated in WA over a 12 year period focusing on patients who received neoadjuvant chemoradiotherapy (NACRT). Methods: Patient details including demographics, histopathology, treatment details, were obtained from the WA sarcoma database (2006‐2018). Progression free survival (PFS) and overall survival (OS) were derived for whole cohort. Results: Twenty seven patients were identified with SS with equal gender incidence. Median age of the cohort was 36 (14‐76) years. The most common primary site of disease was extremity (81.5%). 22/27 patients presented with only localized disease and 59.2% of these received neo‐adjuvant treatment. Of those who received neoadjuvant treatment, 56.2% had NACRT, while 25.0% and 18.7% of patients had chemotherapy and radiotherapy respectively. Mesna, doxorubicin, ifosfamide, dacarbazine (MAID) was the most commonly used chemotherapy regimen as neoadjuvant or adjuvant treatment while ifosfamide (93.7%) was the most commonly used chemotherapy drug in any setting. There was no reported case of disease progression in group of patients who received NACRT apart from one patient who had oligometastatic disease at diagnosis. Median OS of the whole cohort was 38 months while median PFS was 24 months. Bone marrow toxicity was the most commonly reported high grade toxicity in NACRT group (55.5%) but there were no treatment related deaths. Conclusion: NACRT is not widely adopted and treatment is based on institutional preferences, however our data shows that NACRT is a feasible therapy option. NACRT should be evaluated prospectively in a randomized trial.